Family policies and family well-being : the role of political culture - Zimmerman, Shirley (Sage Publications, 1992)
Exploring the connections between family policies, individual and family well-being and political culture, this volume examines several research projects and concludes that their results challenge the view that governmental social programmes in the United States have been detrimental to family life. The results also clarify the relationship between states' political cultures and the kinds of family policies enacted. Additionally, Zimmerman provides guidelines to aid the development of a policy agenda designed to enhance the well-being of individuals and families - regardless of wh.